A Kantian solution to the problem of imperceptible differences. (16th May 2019) - Albertzart, Maike
Abstract: There are cases such as climate change where the cumulative effects of the actions of several agents lead to grave harm but where no individual agent can make a perceptible difference for the better or worse. According to Derek Parfit, dealing with such imperceptible difference cases requires substantial changes to the way we think about morality. In On What Matters, Parfit builds on Kantian Ethics to address the problem of imperceptible differences, but the transformation that Kant's theory undergoes in his hands is radical. I argue that Parfit's changes to Kant's theory are not only unnecessary but also detrimental to making sense of the ethical dimensions of action in collective contexts. Building on the notion of imperfect duties, I offer an alternative solution to the problem of imperceptible difference cases that remains closer to Kant's original theory and avoids the difficulties of Parfit's approach.